2016
DOI: 10.5114/ceji.2016.63132
|View full text |Cite
|
Sign up to set email alerts
|

The era of anti-vascular endothelial growth factor (VEGF) drugs in ophthalmology, VEGF and anti-VEGF therapy

Abstract: Angiogenesis is a clue process for tissue development and function, both in normal and pathological conditions. This process is regulated by multiple molecular systems. One of the most potent is vascular endothelial growth factor (VEGF) and its receptor (VEGFR) system. Members of this family are involved in new vessel formation in embryogenesis and maturation, as well as in reparative or pathological reactions in later stages. They play a substantial role in regeneration, inflammation, wound healing, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 58 publications
1
51
0
2
Order By: Relevance
“…No difference between 1 g -controls and RPM-samples could be observed up until 72 h. VEGF plays an important role in neoangiogenesis, proliferation and migration, mainly of endothelial cells but also of various other cells types [72-74]. VEGF seems to be affected considerably in thyroid cancer cells exposed to s-µ g [72, 75].…”
Section: Discussionmentioning
confidence: 99%
“…No difference between 1 g -controls and RPM-samples could be observed up until 72 h. VEGF plays an important role in neoangiogenesis, proliferation and migration, mainly of endothelial cells but also of various other cells types [72-74]. VEGF seems to be affected considerably in thyroid cancer cells exposed to s-µ g [72, 75].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical evidence indicates a significant correlation between active STAT3 and VEGF in gastric cancer tissues (Choi et al, 2006). Targeting STAT3/VEGF signaling has been suggested as a promising strategy for anticancer treatment (Kim et al, 2015;Po_ zarowska and Po_ zarowski, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] The drugs widely used in intravitreal injection include ranibizumab, Conbercept and bevacizumab, and the primary mechanism is anti-VEGF. 50 Clinical studies found that the anti-VEGF drug ranibizumab in two-thirds of PDR or AMD patients has a good curative effect, but one-third of the cases have an uncertain outcome. 51 We investigated the suppression the proliferation, migration, and invasion of HMEC-1 cells, giving us an opportunity to explore other potential effective therapies.…”
Section: Discussionmentioning
confidence: 99%